1994
DOI: 10.1084/jem.179.2.513
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated human immunodeficiency virus 1 (HIV-1) infection in SCID-hu mice after peripheral inoculation with HIV-1.

Abstract: SummaryA small animal model that could be infected with human immunodeficiency virus 1 (HIV-1) after peripheral inoculation would greatly facilitate the study of the pathophysiology of acute HIV-1 infection. The utility of SCID mice implanted with human fetal thymus and liver (SCIDhu mice) for studying peripheral HIV-1 infizction in vivo has been hampered by the requirement for direct intraimplant injection of H1V-1 and the continued restriction of the resultant HIV-1 infection to the human thymus and liver (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…It has been reported that IL10, but not IL12, can inhibit HIV-1 replication in the SCID-hu Thy/Liv mouse. 25 …”
Section: Screening Anti-hiv-1 Drugs In the Scid-hu Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that IL10, but not IL12, can inhibit HIV-1 replication in the SCID-hu Thy/Liv mouse. 25 …”
Section: Screening Anti-hiv-1 Drugs In the Scid-hu Modelmentioning
confidence: 97%
“…25 In this model, HIV-1 infection can be initiated by intraperitoneal inoculation. 44 However, the Lai/IIIB isolate appears to infect the Thy/Liv organ in this model and leads to thymus depletion.…”
Section: Hiv-1 Env Determinants Required For Efficient Replication Inmentioning
confidence: 99%
“…Mice have been generated by transplantation technologies that maintain human adaptive immune system components including CD4 + T cells that support HIV-1 replication. 134 -136 SCID-hu mice (Severe Combined Immunodeficiency-humanized) 137,138 and BLT mice (Bone Marrow, Liver, Thymus) 139,140 are not necessarily optimal for transmission studies because they retain mouse mucosal and stromal components, and natural routes of HIV-1 transmission begin with mucosal exposure. Another interesting approach has seen the development of multi-layered stratified squamous epithelial membranes (MatTek, Boston, MA) that are derived in an ex vivo differentiation system, using human ectocervical epithelial cells 141,142 or vaginal epithelial cells.…”
Section: Model Systems Using Mixed Human Cell Populationsmentioning
confidence: 99%
“…This hu-Thy/Liv-SCID model has been extensively used for the analysis of human hematopoiesis, especially T cells, and as an animal model of HIV infection (McCune, 1997). HIV-1 injection in the thymic implant of hu-Thy/Liv-SCID mice resulted in significant HIV-1 infection not only in the Thy/Liv implant, but also in the spleen and peripheral blood, which indicated that HIV-1 infection could spread from the thymus to the peripheral lymphoid compartment (Kollmann et al, 1994). The effect of HIV-1 infection on thymocyte maturation and depletion depended upon the strain of HIV-1 infecting the thymus (Kollmann et al, 1995).…”
Section: Humanized Mouse Models To Study Hiv-1 Immuno-pathogenesismentioning
confidence: 99%